The effects of oil price shocks on the prices of EU emission trading system and European stock returns - Krokida, Styliani Iris A.; Lambertides, Neophytos; Savva, Christos S.; Tsouknidis, Dimitris (My University, 2020)
This paper examines whether oil price shocks of different origin affect the price of carbon emission allowance traded under the European Union's Emissions Trading System; leading to changes in aggregate and sector-specific European equity returns. The results show that an unexpected oil-supply disruption has an imminent but weak positive effect on carbon emission price, while a positive aggregate demand shock has a strong positive effect on carbon emission price. By contrast, a positive oil-specific (precautionary) demand shock has a negative but weak effect on carbon emission price. These findings are economically important as positive shocks on the CO2 emission allowance price trigger a decrease on the aggregate stock return of the European equity market, albeit they trigger a large and persistent increase on European equity returns of oil-related industries with the exception of the Energy sector.
Keywords: Emissions trading system; European stock returns; Oil price shocks; Structural VAR